A Study on Different Slot Position for Designing Dual Band Microstrip Antenna for 5G Wireless Communication. Issue 1 (August 2021) - Nasir, N A M; Ja'afar, H; Baba, H; Aziz, N H A
Abstract: In this paper, four antenna designs with different slot positions for dual band frequencies are analysed. A reference antenna operating at 8 GHz is used at a dimension of 30 mm 2 using Rogers RT58880 as the substrate with a dielectric constant of 2.2. Two slots are etched in order to produce a dual band. The antenna resonates at 8 GHz and 15 GHz. Return loss at 8 GHz and 15 GHz are −17.03 dB and −21.37 dB with gain at 7.39 dB at 8 GHz. By using CST Microwave Software, the simulated results are obtained. The slotted antenna produces a dual band antenna that is a suitable candidate for 5G wireless communication tool.